Targeting the innate immune receptor TLR8 using small‐molecule agents. Corrigendum. Issue 9 (2nd September 2020) - Sakaniwa, Kentaro; Shimizu, Toshiyuki
Abstract : The article by Sakaniwa & Shimizu [(2020), Acta Cryst. D76, 621–629] is corrected. Abstract : Three of the figures in the article by Sakaniwa & Shimizu [(2020), Acta Cryst. D76, 621–629] were incorrectly annotated. Corrected figures are published here.